ACP nations sweep development awards - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
ACP countries have chalked up an impressive string of successes in a new sustainable development award, the Supporting Entrepreneurs for Environment and Development..